Sustainability Standards and Sustainable Development – Synergies and Trade‐Offs of Transnational Governance. (31st March 2016) - Brandi, Clara A.
Abstract: This article investigates potential trade‐offs between the socioeconomic and environmental dimensions of development within the context of transnational business governance and sustainability standards, exemplified by smallholder certification in the palm oil sector as a means to improve both sustainability and the inclusion of small farmers in global value chains. This article finds that there are important trade‐offs between environmental sustainability and inclusive development. First, there is a worry that the diffusion of standards that aim at enhancing environmental sustainability may undermine the socioeconomic situation of smallholders by excluding them from global value chains and from international markets that demand certified commodities. Second, while smallholder certification can generate socioeconomic benefits for farmers included in certification schemes, these potential benefits may have contradictory and undesired implications for environmental sustainability. The article analyses these trade‐offs and discusses implications with a view to fostering the synergies between economic, environmental and social sustainability. Copyright © 2016 The Authors Sustainable Development published by ERP Environment and John Wiley & Sons Ltd